Sistema web para la automatización de las operaciones en el centro de retención vehicular del municipio de Loja. - Mora Medina, María Betsabé (2016)
The patio or Retention Center Cars “RCC” are places that have sufficient physical and appropriate space to temporary stay of cars, circumstances under Organic Law of Land Transportation, Traffic and Road Safety "OLLTTS”, should be stay under retention and custody of the State. The cars fleet of Loja (50 000 cars approximate), it can be arrived to this site in any opportunity and can be object of retention by Municipality of Loja RCC. This fact is a necessity to establish a quick and efficient process that enforce what the law stipulates, and the same time permits to contraveners (vehicle´s owners retained) can do the relevant procedures for them to be return your vehicle. In the face of necessity to accelerate the operations that are carried in RCC, appears the possibility to present IT Solution that improve with increased productivity, that this mode of optimize and increase the effectiveness in achieving operative processes of customer service, thought an web system for automation of operations in Retention Center Cars of Municipality of Loja RCC, whose abbreviations has given name to the web system, that simply calls “SACRV”. SACRV Web System developed under the design pattern: Model View Controller “MVC” and the scientist methods, inductive, deductive, descriptive and software development methodology “UWE”. In the development process of the web system that considers a life cycle of incremental software, as indicated by UWE, that begins with obtaining of requirements that determines system functionality through using techniques of recollection as: documental revision, interview and prototyping (the last is used to validate of requirements) , analysis techniques as: interaction matrix, error detection board and recommended actions. To be continued with design phase, in this event that follow UWE models. In the next phase: Coding are made some provided views by the Kruchten Model. Finally, the test phase: functional and acceptance, took place in the facilities of the CRV and the Traffic Unit, they were satisfactory and defined the term of this software project. As the result of application of SACRV Web System facilitates the operations: vehicular entrance by the custodian agent RCC, management of vehicle permanence by the custodian agent and the commission of RCC, Management Process of retained vehicles, that is requested by the vehicle owner and served by the administrator of RCC, and reporting management. Finally, the system provides the mechanisms for accessibility, administration, information and parameterization of the system.